Searches for Dijet Resonances Using √s = 13 TeV Proton-Proton Collision Data Recorded by the ATLAS Detector at the Large Hadron Collider - Beresford, Lydia Audrey (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This book addresses one of the most intriguing mysteries of our universe: the nature of dark matter. The results presented here mark a significant and substantial contribution to the search for new physics, in particular for new particles that couple to dark matter. The first analysis presented is a search for heavy new particles that decay into pairs of hadronic jets (dijets). This pioneering analysis explores unprecedented dijet invariant masses, reaching nearly 7 TeV, and sets constraints on several important new physics models. The two subsequent analyses focus on the difficult low dijet mass region, down to 200 GeV, and employ a novel technique to efficiently gather low-mass dijet events. The results of these analyses transcend the long-standing constraints on dark matter mediator particles set by several existing experiments.